Research on Output Power Quality and Fault Characteristics of Train Traction Inverter - Dongjie JIANG (机车电传动)
The output power quality of the train traction inverter is closely coupled with the working state of the traction system key components. The specific harmonic components generated in the stator current after motor rotor broken bar faults, motor stator inter-turnshort faults, and inverters IGBT open circuit faults was analyzed. Aiming at the stator current fault characteristics, the fault characteristics were identified by fast Fourier transform (FFT), specific harmonic components was extracted, and then a fault diagnosis method that using the ratio of the specific harmonic component content to the fundamental wave content was proposed to locate faulty components. By setting up condition monitoring simulation model of traction system, the correctness and validity of the proposed fault characteristics and the fault diagnosis method were verified.